Sternocleidomastoid muscle activation following inspiratory muscle training in patients with chronic obstructive pulmonary disease: a randomized clinical trial - Diogo Fanfa Bordin; Dannuey Machado Cardoso; Litiele Evelin Wagner; Paula Regina Beckenkamp; Andrea Lúcia Gonçalves da Silva; Dulciane Nunes Paiva (Universidade de São Paulo, 2020)
ABSTRACT This study aims to assess the effect of short-time low frequency inspiratory muscle trainer (Threshold IMT) on inspiratory muscle strength and electromyographic activity of the sternocleidomastoid (SCM) muscle in people with chronic obstructive pulmonary disease (COPD). People with COPD participating in a lung rehabilitation program were allocated to a control or inspiratory muscle training (IMT) group. The control group participated in the usual rehabilitation, whereas the other group received IMT (performed with a load of 50% maximal inspiratory pressure (MIP) adjusted weekly). Both interventions lasted for 2 months. Outcomes included electromyographic analysis of the SCM and MIP. In total, ten participants were allocated to each group. The IMT group presented an increase in absolute (p<0.001) and predicted (p<0.001) values of MIP and also in pre- and post-intervention variation between groups (p=0.003 and p=0.008, respectively). Such differences were not found in the control group. The SCM muscle activity decreased in the IMT post intragroup evaluation (p=0.008). IMT provided a reduction of the electromyographic activity of SCM in COPD patients, also increasing inspiratory muscle strength in the study participants.